PEMAHAMAN KONSEP SISWA DITINJAU DARI KECERDASAN MATEMATIS LOGIS - Ayu Silvi Lisvian Sari; Cicik Pramesti; Suryanti Suryanti; Riki Suliana Ranggawati Sidik (Jurnal Numeracy, 2022)
The purpose of this study is to determine high school students' understanding of the concept in terms of logical-mathematical intelligence. This study's subjects were three students, one from each of three groups of students with high, medium, and low logical-mathematical intelligence. The indicators of understanding concepts used in this study are Bloom indicators of understanding concepts, namely translation, interpretation, and extrapolation with Krulik and Rudnik problem-solving procedures. This study's instruments were tests and interviews. Data analysis consists of three steps: data reduction, data presentation, and conclusion. According to the findings of the analysis, (1) students with high logical-mathematical intelligence met the three indicators of concept understanding, namely the indicators of translation, interpretation, and extrapolation, as well as the five Krulik indicators of problem-solving. (2) students with high logical-mathematical intelligence fulfilled the three indicators of concept understanding, namely indicators of translation and interpretation, with 4 of 5 indicators of problem-solving according to Krulik and Rudnik fulfilled, (3) students with low logical-mathematical intelligence fulfilled one of the three indicators of concept understanding, namely indicators of translation, with 3 of 5 indicators of problem-solving according to Krulik and Rudnik fulfille. Abstrak Penelitian ini bertujuan untuk mengetahui pemahaman konsep siswa SMA ditinjau dari kecerdasan matematis logis. Subyek dalam penelitian ini terdiri dari tiga orang siswa yang masing-masing dari kelompok siswa dengan kecerdasan matematis logis tinggi, sedang dan rendah. Indikator pemahaman konsep yang digunakan dalam penelitian ini merupakan indicator pemahaman konsep menurut Bloom, yaitu Penerjemahan (translation), Penafsiran (Interpretation), Ekstrapolasi (extrapolation) dengan prosedur pemecahan masalah menurut Krulik dan Rudnik. Instrumen yang digunakan dalam penelitian ini adalah Tes dan wawancara. Analisis data mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil analisis menyatakan bahwa (1) siswa dengan kecerdasan matematis logis tinggi memenuhi ketiga indikator pemahaman konsep yaitu indikator penerjemahan, penafsiran, dan ekstrapolasi dengan 5 indikator pemecahan masalah menurut Krulik dan Rudnik terpenuhi, (2) siswa dengan kecerdasan matematis logis sedang memenuhi ketiga indikator pemahaman konsep yaitu indikator penerjemahan, dan penafsiran dengan 4 dari 5 indikator pemecahan masalah menurut Krulik dan Rudnik terpenuhi, (3) siswa dengan kecerdasan matematis logis rendah memenuhi satu dar tiga indikator pemahaman konsep yaitu indikator penerjemahan dengan 3 dari 5 indikator pemecahan masalah menurut Krulik dan Rudnik terpenuhi.